ISOLASI DAN IDENTIFIKASI ZAT ANTIBAKTERI DALAM EKSTRAK KELOPAK BUNGA ROSELA (HIBISCUS SABDARIFFA L.) - , LISA SOEGIANTO, Dr. rer. nat. Triana Hertiani, M.Si., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Rosella (Hibiscus sabdariffa L.) calyx extract has been known to possess antibacterial effects against several pathogenic microbes. Considering that microbes can be found in biofilm state which relatively more ressistant to antibiotics, a research to explore the potency of Rosella as a source of antibacterial which are potential against planktonic and biofilm states is needed. This study aimed to isolate and identify the antibacterial active substance form Rosella calyx extract by using planktonic growth and biofilm formation inhibition of Staplylococcus aureus and Eschericia coli, as well as quorum sensing inhibition assay towards Pseudomonas aeruginosa as bioassay guidances. Rosella calyces powder was macerated with ethanol 70% - HCl (99:1)v/v and then successively fractionated using n-hexane, ethyl acetate, n-butanol and water. Fractions were tested by using diffusion method to evaluate the effect on bacterial growth inhibition, biofilm inhibition with microdillution assay and quorum sensing inhibition by diffusion technique. The most active fraction was fractionated further by using vacuum liquid chromatography and preparative thin layer chromatography methods to purified the active compound. Bioautography was used to identify the active spot on TLC. Isolate was evaluated its purity by using densitometry and LCMS. Structure characterization was done by using NMR, IR and UV spectroscopy methods. The results showed the ethyl acetate fraction as the most active fraction in bacterial growth inhibition with the inhibition zone observed in S. aureus, 15.89 Â± 0.37 mm (2 mg/well) and 15.93 Â± 0.72 mm (4 mg/well), while in E. coli, 17 Â± 0.86 mm (2 mg/well) and 17.35 Â± 0.48 mm (4 mg/well). In the antibiofilm assay, % inhibition of ethyl acetate fraction towards S. aureus biofilm formation was 62.05% Â± 17.83, while 11.11% Â± 23.13 was detected against E. coli. In the quorum sensing inhibition assay, pyocianin formation inhibition was detected in P. aeruginosa as 24.65 Â± 1.82 mm (2 mg/well) and 26.15 Â± 1.02 mm (4 mg/well). Isolateâs structure characterization recommend that the isolate was a benzofuran derivate.